WORK VALUE PADA KARYAWAN DITINJAU DARI BUDAYA ETNIS FLORES - Debi Angelina Br Barus (Psychopedia Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2022)
This study aims to determine differences in work values in terms of ethnic Flores. The subjects in this study were 127 employees who came from the Flores ethnicity. This study uses a comparative quantitative research approach. The results showed that there were differences in the work value of employees in terms of ethnicity on the island of Flores. This is evident from the results of statistical tests, namely the significance test < 0.05, which is 0.000 < 0.05. This is also evident from the results of the mean (average) b test for each ethnic group. Where the mean value (average) of the ethnic Sikka Krowe 157.13 the value is higher and the lowest mean value (average) is the ethnic Flotim with a value of 145.55. Keywords: Work value, Flores island ethnicity, employess Penelitian ini bertujuan untuk mengetahui perbedaan nilai kerja ditinjau dari etnis Flores. Subjek dalam penelitian ini adalah 127 karyawan yang berasal dari etnis Flores . Penelitian ini menggunakan pendekatan penelitian kuantitatif komperatif. Hasil penelitian menunjukkan adanya perbedaan work value (nilai kerja) karyawan ditinjau dari etnis yang ada di pulau flores. Hal ini terbukti dari hasil uji statistik yaitu uji signifikansi < 0.05 yaitu 0.000 < 0.05. Hal ini juga terbukti dari hasil uji mean (rata-rata)b tiap etnis berbeda. Dimana nilai mean (rata-rata) dari etnis Sikka Krowe 157.13 nilainya lebih tinggi dan nilai mean (rata-rata) terendah ada pada etnis Flotim dengan nilai 145.55. Kata Kunci: Work value, Etnis pulau Flores, Karyawan